Formulasi dan Evaluasi Fisik Sediaan Emulgel Tabir Surya Ekstrak Kulit Batang Kayu Manis (Cinnamomum burmannii) - Risqika Yuliatantri Paramawidhita; Uswatun Chasanah; Dian Ermawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
One of the natural ingredients can be used for sunscreen is Cinnamomum burmannii. Sinamaldehid chemical constituents in cinnamon bark extract that has potential as an antioxidant and can be used as a sunscreen content. This study was to determine the levels of cinnamon bark extract ( 1 %, 2 % and 3 % ) which can give physical characteristics, acceptability, which is optimal for preparations with HPMC as a gelling agent, Evaluations include pH, the power spread, the viscosity and acceptability. The results of organoleptic for formula I (1%), II (2%) and III (3%) have a soft texture grainy, the distinctive smell of cinnamon, and all formula has a pale brown color. From the analysis of One-Way ANOVA found significant differences for any dispersive power. But did not have significant differences in pH and viscosity. For acceptability evaluation formula III is the optimal formula to applied softness, easiest formula to flattened and easy to wash.